Sphogsorb: Biodegradable Adsorbent for Oil and Grease Trap - Saiful Azhar, Saad; Salsuwanda, Selamat; Che Zulzikrami, Azner Abidin; Kamarudin, Hussin, Brig. Gen. Dato' Prof. Dr.; Khairul Nizar, Ismail, Dr.; Abdul Haqi, Ibrahim (Malaysian Invention and Design Society (MINDS), 2010)
Saiful Azhar Saad and his team won silver at ITEX 2007, 18th - 20th May 2007 was held at Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur.